Existential isolation and the struggle for belief validation. (9th September 2021) - Long, Anson E.; Pinel, Elizabeth C.; Daily, Jeff R.; Costello, Abby E.
Abstract : People exhibit a strong need for belief validation, which they meet by sharing reality with others. Here, we examine the hypothesis that existential isolation – feeling alone in one's experiences – interferes with people's ability to share reality and thus achieve validation for their beliefs. In Studies 1 and 2, participants read a scenario that presented a choice, rated the percent of their peers whom they thought would select each of the two options, and then reported their own choice and their certainty of it. Existential isolation was a significant negative predictor of expected agreement and certainty in both studies. Interpersonal isolation (i.e., loneliness) did not relate to either of these variables. Moreover, mediational analyses from Study 2 show that expected agreement mediated the relationship between existential isolation and certainty in the hypothesized manner: existential isolation predicted high levels of uncertainty because people high in existential isolation tended not to believe that others would make the same choice. In Study 3, existential isolation correlated negatively with expected agreement even after controlling for interpersonal isolation, self‐esteem, and depression. The findings attest to the epistemic implications of existential isolation and provide insight for future research.